School Boards : From Warper Planks to Polished Mahogany - Paulson, Daniel R., (Brill Guides to Scholarship in Education ;, 2025)
You want to be on the school board, or you are on the board, but it is chaos and frustration. My time on a school board and my years in education have taught me some lessons in this book. I got there to do something, but then I found that I was only one of nine and had no authority to tell anyone what to do. You must learn to work with the district administrator and other board members. Common sense is essential but insufficient to navigate the conflicting evidence and views on issues vital to student achievement.